Teacher trainers: The challenge of teaching to teach - Lorenzo, María Gabriela (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
To transform and to transpose the constructed knowledge in the field of scientific research in alternatives or proposals that may be implemented at the classroom level is a challenge for Science Education research. This paper attempts to show how the contributions of research in this field can help us fulfill our teaching with high quality and efficiency. We organize this presentation proposing a model for theorizing about the training of chemistry teachers, the BiPiT, which combines the chemical triangle with the proposal of pedagogical content knowledge. Along the same we will reflect on the close relations between teaching and learning, suggesting a back and forth between the chemistry teaching, Chemistry and teaching.